Strategi Pengembangan Usahatani Jagung di Desa Sinarsabungan Kecamatan Bonatua Lunasi Kabupaten Toba - SINURAT, FEBRYANTY; BUDIASA, I WAYAN; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Corn Farming Development Strategy in Sinarsabungan Village, Bonatua Lunasi District, Toba Regency. Corn is one of the prime commodities in Sinarsabungan Village. The development of corn farming business until now has not increased significantly due to the lack of knowledge of farmers, the use of low technology and so on. The purpose of this study is to identify the internal and external conditions of corn farming, analyze several corn farming development strategies and formulate the priority strategy for developing of corn farming in Sinarsabungan Village. The method used in this study is a descriptive analysis, SWOT analysis and QSPM analysis. The results of the analysis obtained for the internal factors are the main strengths in corn farming that are road access and good transportation (0,53). The main weakness is the limited capital of farmers (0,20). For the external factors that are the main opportunities, namely an increase in market demand and an increase in corn prices (0,70). The main threat is that the support of agricultural extension workers for corn has never been implemented (0,36). Based on the results of the analysis, the priorities of the selected strategy are: the need for the role of the government in providing capital institutions and intensifying the role of agricultural extension workers for corn cultivation.